X-Linked Retinoschisis: RS1 Mutation Severity and Age Affect the ERG Phenotype in a Cohort of 68 Affected Male Subjects - Bowles, Kristen; Cukras, Catherine; Turriff, Amy; Sergeev, Yuri; Vitale, Susan; Bush, Ronald A.; Sieving, Paul A. (Investigative ophthalmology & visual science, 2011)
To assess the effect of age and RS1 mutation on the phenotype of X-linked retinoschisis (XLRS) subjects using the clinical electroretinogram (ERG) in a cross-sectional analysis. Sixty-eight XLRS males 4.5 to 55 years of age underwent genotyping, and the retinoschisis (RS1) mutations were classified as less severe (27 subjects) or more severe (41 subjects) based on the putative impact on the protein. ERG parameters of retinal function were analyzed by putative mutation severity with age as a continuous variable. The a-wave amplitude remained greater than the lower limit of normal (mean, -2 SD) for 72% of XLRS males and correlated with neither age nor mutation class. However, b-wave and b/a-ratio amplitudes were significantly lower in the more severe than in the less severe mutation groups and in older than in younger subjects. Subjects up to 10 years of age with more severe RS1 mutations had significantly greater b-wave amplitudes and faster a-wave trough implicit times than older subjects in this group. RS1 mutation putative severity and age both had significant effects on retinal function in XLRS only in the severe mutation group, as judged by ERG analysis of the b-wave amplitude and the b/a-ratio, whereas the a-wave amplitude remained normal in most. A new observation was that increasing age (limited to those aged 55 and younger) caused a significant delay in XLRS b-wave onset (i.e., a-wave implicit time), even for those who retained considerable b-wave amplitudes. The delayed b-wave onset suggested that dysfunction of the photoreceptor synapse or of bipolar cells increases with age of XLRS subjects.